APLIKASI METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PERSEDIAAN BBM DI PT. SARANA SAMUDERA PACIFIC BITUNG - Veyro E.L Lumempouw; Hengky Luntungan; Charles Chevy Punuhsingon (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2012)
Supplies have an important role in every company. Supplies would make the company running well. As well as supplies must be provided continually so that the company can operating well and the consumer demand would be fulfilled.The purpose of this research is to determine the model and to design the supplies of diesel fuel at PT. Sarana Samudera Pacific Bitung. Using the EOQ (Economic Order Quantity) formula could minimize the total cost or the overall cost of supplies at the company.From the calculation of the total cost of supplies using the formula, we got a result that the overall cost is Rp. 2.395.785.138,-. The company’s calculation is Rp. 2.403.022.632,-, which means company can save Rp. 7.237.494. It can be concluded that using EOQ formula can minimize the total cost at PT. Sarana Samudera Pacific.Key words: Supplies, Diesel Fuel, EOQ.